Métodos de ajuste da função Weibull e seu desempenho na prognose do crescimento e produção de Eucalyptus dunnii - Felde, João Luiz (2010)
The main objective of this research was to develop a simulator system of growth and yield for unthinned plantations of Eucalyptus dunnii using different adjustment methods for the Weibull probability density function to describe the forest structure at various ages. The data used in this research came from measurements of 239 plots in E. dunnii stands in the region of Telêmaco Borba, PR, owned by Klabin S.A., aged from 3 to 20 years. The 3P Weibull function parameters were obtained for each plot, adjusting it by the maximum likelihood estimator method and by the moment method form modified to recognize the data distribution asymmetry, and also adjusting the 2P and 3P Weibull function by the moments method in the traditional way. The adjustments by plot were assessed by the Kolmogorov-Smirnov adherence test, Reynolds index, and the estimate standard error. Equations were tested to predict the dominant height according to age and construction of site index curves, equations to represent the hypsometric relationship at various ages and also stand attributes were modeled to express the survival, basal area, minimum diameter, maximum diameter and diameters variance. The statistics indicated that the maximum likelihood estimator method was less accurate in estimating the frequency of trees in each diameter class. The adjustment by the moments method, in its modified form to recognize the asymmetry of the data, presented values very similar to those obtained from the adjustment of 3P function by the moments method in its traditional form. Comparing the fitting of the two and three parameters function, the Weibull 2P was more accurate, with better statistics. After modeling the stand attributes, a growth and yield simulator of E. dunnii was built, using the Weibull function to estimate the trees frequency in each diameter class, and consequently the production volume in each of these. The Weibull function with two and three parameters was used in simulations, and the frequencies obtained in each simulation were compared with the mid observed frequencies in the data set in various age-site combinations, applying the L&O identity test. The identity test statistics showed that 21% of the simulations that used the 3P Weibull function had identity among estimated and observed frequencies in each age-site combination. For simulations that used the 2P Weibull function, the percentage of identity among the observed and estimated values was 30%, indicating superiority of the two parameters function use in simulations of the diameter class frequency.